An annotated list of fish genetic resources of Faizabad District, U. P. - Pandey, A C (Indian Journal of Fisheries, 2011)
As many as 74 species of freshwater fishes have been recorded from Faizabad District. Apart from these native ichthyofauna, some exotics like grass carp, silver carp, bighead, common carp and exotic magur have also been transplanted in the district for aquaculture. Out of 79 fin fishes, 25 are of major and 21 of minor commercial importance for food and game purposes whereas the others are considered as weed or forage fish.